Pedagogical Conditions of Forming Natural-Scientific Competence of the Future Ecologists - Halyna Biletska (Pedagogical Discourse, 2014)
It is grounded in the article that forming natural-scientific competence of the future ecologists can be guaranteed under the following pedagogical conditions: renovation of the content of natural-scientific preparation; introduction of the technologies of teaching with the use of informational educational environment, which offers broad access to the educational resources, guarantee the abilities for self-education and realization of individual educational path; availability of teaching-methodological providing for the formation and evaluation of the state of forming natural-scientific competence; ability of the teacher to conduct educational process using modern educational technologies, to create conditions for the manifestation of independence, initiativeness and creative work of students; forming equal partnership relations of the student and the teacher.